FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - Sugiarto Prajitno; Vionita Vionita (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2020)
The intent of this research is  obtained empirical evidence related to several factors that influence earnings management. The independent variable used in this research are firm size, firm age, firm financial leverage, audit quality, board of director, board of commissioner, audit committee meetings, managerial ownership, profitability, and firm growth, with the dependent variable earnings management. Non financial companies listed on the Indonesia Stock Exchange(BEI) during 2014 until 2018 are the object of this research. The data used are secondary data (financial statement and annual report) from www.idx.co.id. Purposive sampling method is used in the sample selection. Sixty two companies which match the criteria are used as the research sample. This research use multiple regression in observing the effect of each variable. The results of this research indicate that firm size, firm age, board of commissioner, and firm growth influence earnings management. While firm financial leverage, audit quality, board of director, audit committee meetings, managerial ownership, and profitability do not affect earnings management.